PERILAKU PENCARIAN PELAYANAN KESEHATAN TERKAIT DETEKSI DINI HIV/AIDS PADA WANITA PENJAJA SEKS DI SAWAN BULELENG - I Putu Yoga Apriadi; Made Oka Ari Kamayani; Made Rini Damayanti (Coping: Community of Publishing in Nursing, 2016)
HIV/AIDS is an infectious disease that is becoming a global health problem today. This causes disease prevention is a top priority in avoidance of AIDS and infection of HIV virus that focus on key populations (FSW). Voluntary Counselling and Testing (VCT) is a strategy to prevent the spread of HIV / AIDS. This study used a qualitative approach with a thematic analysis technique to describe and explore health seeking behavior related to early detection of HIV/AIDS among FSW in Sawan, Buleleng Regency. The data was collected (May - June 2015) using in-depth interviews and field observations. Sampling technique used purposive sampling by the number of six participants. The results showed FSW knowledge about HIV/AIDS are still common and have not focused that influence risky sexual behaviors of FSW such as anal sex and oral sex that don’t use condoms. FSW health care view such as health care workers, health care, and special clinics is quite good. Motivating factor in the behavior in seeking health care is the awareness and the desire of the FSW itself, support for the FSW, and an invitation from a friend. FSW inhibiting factor in the behavior in seeking health care is the cost of health care, examination results, lack of information, health care facilities, and partner check. Based on this research, government and health workers together were able to intensify early detection of health services related to HIV/AIDS to suppress the incidence of AIDS, especially in FSW that have a high risk of HIV/AIDS.